HABILIDADES SOCIALES EN EL DESARROLLO PSICOEMOCIONAL EN ESTUDIANTES DE CUARTO “A” Y QUINTO “A” DE LA CARRERA DE PSICOLOGÍA EDUCATIVA. UNACH. PERÍODO OCTUBRE 2018 - MARZO 2019 - Pala Calero, Marco Omar (2019)
The objective of this research project was to determine the relationship of social skills and psycho-emotional development in students of the National University of Chimborazo in the city of Riobamba. In theory social skills are a set of cognitive-behavioral skills that facilitate the human being to have positive, assertive relationships which are favorable with other human beings, on the other hand psycho-emotional development indicates that it is the ability to perceive accurately, value express emotions and access or generate feelings that facilitate a sane thinking, therefore have the ability of emotional understanding and emotional knowledge, methodologically a non-experimental design was used, by the type of descriptive research, Correlational, for the transverse time, the population were the students of the career of educational psychology, the sample was not probabilistic and intentional because it was worked with 54 students of fourth and fifth semester, the technique used were the Scale of Social Skills EHS of Elena Gismero González and the Tmms24 Scale of Saloyev and Mayer, well, you could get the d Atos and results conclude that there is a positive correlation between social skills and psycho-emotional development because students see the need to improve emotional behaviors, empathy, assertiveness and self-concept of each will be balanced so that be more honest, equitable and integrated people in the educational environment, benefiting their inter and intrapersonal relationships.